A Translation Strategy Analysis Used In The Kite Runner Novel - Iskartika, Fasih, Dr. Dwi Haryanti, M.Hum, Siti Fatimah, S. Pd, M. Hum (2016)
This research focuses on the translation strategies on The Kite Runner novel by Khaled Hosseini. The objectives of this research are (1) to classify the translation strategies used by the translator in The Kite Runner novel and its translation, and (2) to describe the translation equivalence of translation strategies found in The Kite Runner novel and its translation. The research type applied in this study is descriptive qualitative type. The object of the research is The Kite runner novel. The data is sentence found on The Kite Runner novel and its translation. The technique of collecting data in this study is documentation and interviewing. The writer uses triangulation to prove the validity of the research. The results of this research shows that first, the writer finds 7 types from 8 types of translation strategies according to Baker‟s theory, there are translation by a more general word, translation by a more neutral/less expressive word, translation by cultural substitution, translation using a loan word or loan word plus explanation, translation by paraphrase using related word, translation by paraphrase using unrelated words, and translation by omission. From 1030 data, there are 182 or 17,66%% data belong to Translation by a more general word, 151 or 14,66% data belong to Translation by a more neutral/less expressive word, 25 or 2,42% data belong to Translation by cultural substitution, 375 or 36,40% data belong to Translation using a loan word or loan word plus explanation, 64 or 6,21% data belong to Translation by paraphrase using a related word, 110 or 10,67% data belong to Translation by paraphrase using unrelated word, 123 or 11,94% data belong to Translation by omission. Second, in this research, the researcher states that the translation in The Kite Runner novel has been equivalence with the target language. From 1.030 analyzed data, there are 1030 data or 100% equivalence translation and none of non-equivalence translation. From the preceded percentages, it can be seen that the translation strategies found in The Kite Runner novel and its translation is an equivalence translation. Keywords: translation, translation strategies, equivalence.